نظم المعلومات الإدارية التربوية - Abdul Malik Karim Amrullah; Zenib Mohamed M AlFegeh (Abjadia, 2016)
نجاح المؤسسات التربوية في عصر العولمة يعتمد على نظام إدارة المعلومات التعليم الذي هو ممارسات استخدام دقيقة وذات مصداقية وفعالة. نتائج هذه الدراسة تشير إلى أهمية نظام المعلومات والتعليم ودور كبير في تطوير وتحديث التعليم في خضم التغيرات العالمية والمحلية. نظام إدارة المعلومات التعليم قادرة على توفير كل المعلومات التي تحتاجها الإدارات المختلفة للعمليات الإدارية والقياس الإحصائي، وتحديد المشكلة، والسيطرة على نوعية التعليم وتطوير الاستثمار والاتصالات. مع هذا، يمكن لكل مرب تعزيز أنفسهم وتبادل المعلومات وذلك لخلق جو يفضي يدعم نجاح إدارة التعليم في تحديد الإدارة التربوية.The success of educational institutions in the era of globalization depends on the education information management system that is accurate, credible, and efficient usage practices. The results of this study indicate the importance of education information system and great role in the development and modernization of education in the midst of global and local changes. Education information management system able to provide all the information needed by the various departments for administrative processes, statistical measurement, problem identification, control the quality of education and develop investment and communication. With this addition, every educator can promote themselves and exchange information so as to create a conducive atmosphere that supports the success of education management in deciding policy.